An isoquinoline alkaloid, Protopine from Corydalis govaniana growing in Himalayan region of Nepal - Shrestha, R. L.; Jha, R. N. (Journal of Nepal Chemical Society, 2013)
Chemical investigation of the roots of Corydalis govaniana resulted in the isolation and characterization of one isoquoniline alkaloid, protopine(1). The structure was established on the basis of extensive spectroscopic data analysis and comparison with spectroscopic data reported. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8116 Journal of Nepal Chemical Society Vol. 28, 2011 Page: 106-109 Uploaded Date: May 24, 2013